MANIFESTASI KLINIS DAN LABORATORIS PENDERITA SINDROMA GUILLAIN BARRE DI RUANG PERAWATAN ANAK RSU DR. SAIFUL ANWAR MALANG - Muid, Masdar (Jurnal Kedokteran Brawijaya, 2005)
ABSTRACT Guillain Barre Syndrome is one of the leading diseases from Acute Flaccid Paralysis after the decrease in poliomyelitis. InGuillain Barre Syndrome, the motoric muscles becomes weak and it could also attack the respiratory muscle which is lifethreatening to patients. The objective of this study is to report Guillain Barre Syndrome cases from June 1999 until June2005 based on the clinical manifestation and laboratory in children care unit of dr. Saiful Anwar hospital. In this researchthere were 38 Guillain Barre Syndrome cases which were diagnosed using the Gilroy and Meyer criteria. 22 patients(57,9%)  were  male,  16  patients  (42,1%)  were  female.  18  patients  (43,36%)  were  below  5  years  of  age,  13  patients(34,21%) were between 5 to 10 years of age and 7 patients (18,42%) were between the age of 10 to15 years. The mostcommon infection that precedes was upper respiratory infenction which amounts to 32 cases (84,21%). The latent phasebetween 8 to 14 days were 11 patients (28,94%) and 15 to 21 days were 22 patients (57,89%). The progresive phase 1 to7 days occured in 17 patients (44,73%), 8 to 14 days also in 17 patients (44,73%).The clinical features were paresthesiasfollowed by weakness to 23 patients (60,52%) and weakness only in 15 patients (39,47%). The pattern of weakness bytetraparese  in  5  patients  (13,15%)  and  paraparese  in  33  patients  (86,84%).  The  distribution  of  weakness  was  more